1985
DOI: 10.1530/jrf.0.0750593
|View full text |Cite
|
Sign up to set email alerts
|

Karyotypes of 3- or 4-day-old pig embryos after short in-vitro culture

Abstract: Summary. Pig embryos (3\p=n-\4days old) were

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
2

Year Published

1989
1989
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 16 publications
1
11
2
Order By: Relevance
“…As for comparison of our findings with previous data obtained in pigs by karyotyping, we can compare the total number of aberrant embryos detected. Our finding of 11.4 % approximates the data published by McFeely (1967) and by Van der Hoeven et al (1985) who detected 9.4 and 7.3 % of aberrant embryos, respectively.…”
Section: Discussionsupporting
confidence: 90%
“…As for comparison of our findings with previous data obtained in pigs by karyotyping, we can compare the total number of aberrant embryos detected. Our finding of 11.4 % approximates the data published by McFeely (1967) and by Van der Hoeven et al (1985) who detected 9.4 and 7.3 % of aberrant embryos, respectively.…”
Section: Discussionsupporting
confidence: 90%
“…The embryo is regarded as 0Y. embryos, ploidy anomalies were seen in 7.3% of embryos [Van der Hoeven et al, 1985]; however, in in vitro embryos, the ploidy anomaly rate increased to 45.9% [Ulloa et al, 2008]. To explain this, an increased frequency of aneuploidies in embryos produced in vitro in comparison to those obtained in vivo was evidenced [Slimane-Bureau and King, 2002].…”
Section: Discussionmentioning
confidence: 99%
“…Embryos produced by IVP have a high incidence of chromosomal abnormalities, including mixoploidy and polyploidy; these have been linked to a high frequency of polyspermic fertilization [12][13][14]. Cytogenetic analysis of porcine blastocysts produced in vitro has revealed that about 40% of the blastocysts are abnormal [15]; this is higher than the 7.3% reported for in vivo-derived embryos [16]. In cattle, the incidence of mixoploidy is about three times higher in embryos produced by IVP than in those produced in vivo [17].…”
mentioning
confidence: 91%